О каламбурном предлоге с (The Witty Russian Preposition s) - Lennart Lönngren (Poljarnyj Vestnik: Norwegian Journal of Slavic Studies, 2004)
The Russian preposition s (with the instrumental case) exhibits an am- biguity which makes it apt for being used in puns and anecdotes. In cer- tain contexts it oscillates between a more semantic function (comitative meaning in a broad sense) and a more syntactic. In the latter case it forms a preposition phrase which fills an actant position of another predicate.